Turawa Reservoir in southern Poland – An example of the threat to dammed reservoir ecosystems - Andrzej Kłos; Mirosław Wiatkowski; Witold Skorulski; Maria Strzelczyk; Ryszard Polechoński; Barbara Wróbel; Jakub Dobrzyński; Czesława Rosik-Dulewska; Aleksandra Steinhoff-Wrześniewska; Agnieszka Dołhańczuk-Śródka; Zbigniew Ziembik; Łukasz Gruss; et al. (Desalination and Water Treatment)
A study of the ecological potential and the chemical pollution of the Turawa Reservoir (southern Poland), as well as an assessment of the pollution of its recharge waters, was carried out between 2019 and 2021. The reservoir was chosen because of the eutrophication process that has been ongoing for several decades. Phytoplankton, phytobenthos and macrozoobenthos were surveyed as part of the ecological potential assessment. Analysed indicators were: BOD5, CODCr, nitrogen concentrations (Kjeldahl nitrogen TKN, ammonium nitrogen NH4-N, nitrate nitrogen NO3-N and total nitrogen TN) and phosphorus (orthophosphate phosphorus PO4-P and total phosphorus TP), as well as conductivity and water pH. Using ion chromatography, the ionic composition and heavy metal concentrations. Coliforms, faecal enterococci and Salmonella spp. were also assessed. The condition of the reservoir water was assessed as poor. The poor quality of the water supplying the reservoir, and the bottom sediments, in which large quantities of, among other things, nutrients and heavy metals have accumulated over the years, have been identified as the cause. A factor related to biomass accumulation was also identified. The problem outlined characterises most European dam reservoirs, especially shallow reservoirs with low thermal stratification.